Effectively Improve the Astaxanthin Production by Combined Additives Regulating Different Metabolic Nodes in Phaffia rhodozyma - Li, Zhipeng; Yang, Haoyi; Zheng, Chenhua; Du, Xiping; Ni, Hui; He, Ning; Yang, Liang; You, Li; Zhu, Yanbing; Li, Lijun (Frontiers in Bioengineering and Biotechnology, 2022)
Astaxanthin is an important natural resource that is widely found in marine environments. Metabolic regulation is an effective method for improving astaxanthin production in Phaffia rhodozyma. Most studies have focused on single regulators, which have limited effects. In this study, 16 metabolic regulators were screened to improve astaxanthin production in high-yield and wild-type strains. Fluconazol and glutamic acid increased astaxanthin volumetric yield in MVP14 by 25.8% and 30.9%, respectively, while ethanol increased astaxanthin volumetric yield in DSM626, 29.3%. Furthermore, six additives that inhibit the competing pathways and promote the main pathway for astaxanthin synthesis were selected for combination treatment. We found that the optimal combination was penicillin, ethanol, triclosan, and fluconazol, which increased astaxanthin cell yield by 51%. Therefore, we suggest that simultaneously promoting the master pathways (mevalonate) and inhibiting competing pathways (fatty acid synthesis and ergosterol) is the best strategy to improve astaxanthin cell yield. Moreover, regulators of the biomass pathway should be avoided to improve cell yield. This study provides a technical basis for the utilisation of astaxanthin in P. rhodozyma.